2014
DOI: 10.1155/2014/568741
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization, and Biological Activity Studies of Ni(II) and Zn(II) Complexes

Abstract: Ni(II) and Zn(II) complexes were synthesized from tridentate 3-formyl chromone Schiff bases such as 3-((2-hydroxyphenylimino)methyl)-4H-chromen-4-one (HL1), 2-((4-oxo-4H-chromen-3-yl)methylneamino)benzoic acid (HL2), 3-((3-hydroxypyridin-2-ylimino)methyl)-4H-chromen-4-one (HL3), and 3-((2-mercaptophenylimino)methyl)-4H-chromen-4-one (HL4). All the complexes were characterized in the light of elemental analysis, molar conductance, FTIR, UV-VIS, magnetic, thermal, powder XRD, and SEM studies. The conductance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The presence of oxygen and nitrogen in the coordination sphere was further confirmed by the presence of ν(M―O) and ν(M―N) bands which appeared in the ranges 510–560 and 450–488 cm −1 , respectively . The FT‐IR results showed that the Schiff base ligand acted as tridentate chelating ligand as it coordinated to metal ions through nitrogen of azomethine group, oxygen of carboxylate group and nitrogen of imidazole ring.…”
Section: Resultsmentioning
confidence: 84%
“…The presence of oxygen and nitrogen in the coordination sphere was further confirmed by the presence of ν(M―O) and ν(M―N) bands which appeared in the ranges 510–560 and 450–488 cm −1 , respectively . The FT‐IR results showed that the Schiff base ligand acted as tridentate chelating ligand as it coordinated to metal ions through nitrogen of azomethine group, oxygen of carboxylate group and nitrogen of imidazole ring.…”
Section: Resultsmentioning
confidence: 84%
“…Complex [Zn ( 58 ) 2 ]⋅H 2 O (IC 50 = 0.69 µg/mL) exhibited comparable antioxidant activity to BHT (butylatedhydroxyltoluene) (IC 50 = 0.67 µg/mL), which was a standard drug. The complexes [Ni ( 55 ) 2 ], [Ni ( 58 ) 2 ], and [Zn ( 58 ) 2 ]⋅H 2 O showed moderate antioxidant activity in comparison to the rest of complexes, antioxidant activity of which was weak [ 268 ].…”
Section: Antioxidant Complexes Of Flavonoids Coumarins Chromones With Metal Ionsmentioning
confidence: 99%
“…Imine ligands with sulfur and nitrogen donor atoms in their structures are effective metal chelating agents and have a wide range of therapeutic applications [ 6 , 7 , 8 ]. Imine compounds produced from 2-aminothiophenol, 2-aminophenol, 2-aminobenzoic acid, and 2-amino-3-hydroxy pyridine, in particular, have antipathogenic activity, inhibition of protein tyrosine phosphatases, and nuclease activity [ 9 ]. These activities could be owing to the inclusion of both hard and soft donor groups in a single ligand, which boosts the potential to coordinate with both hard and soft acidic metals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%